The Gastrointestinal Parasite Cow in The Work Area of UPTD Laboratory of Animal and Veterinary Public Health in Jambi Province in 2020-2022 - Sarwo Edy Wibowo; Yudhi Ratna; Aan Awaludin; Fathur Rohman Haryadi; Zurbein Zurbein (Universitas Airlangga, 2023)
Background: Jambi Province consists of 11 regencies and cities, which have a quite high potential for cattle breeding because the availability of natural feed for livestock is still very abundant. Jambi province has high rainfall and humidity. High rainfall and humidity cause the growth of helminth eggs, which can infect the digestive tract of cows. Helminths infestation in the digestive tract can cause damage to the intestinal mucosa, which can reduce the efficiency of absorption of food, causing a loss in cattle productivity in body weight, milk production, and meat quality. Purpose: This study aimed to determine the incidence of helminthiasis and the types of worms that infect livestock in the work area UPTD Laboratory of Animal and Veterinary Public Health Jambi Province. Methods: A total of 2.720 feces were screened for parasite digestive tract in this study using floating and sedimentation methods. Results: It was found that the highest prevalence in 2020 occurred in Bungo Regency, which was 4.47%, while the lowest was in Sarolangun Regency, which was 0%. In 2021, the highest prevalence was in Jambi City, which was 7%, while the lowest was in Tanjung Jabung Barat Regency, which was 0.28%. The highest prevalence in 2022 will be in Jambi City, which is 6.19%, while the lowest will be in Sungai Full City, which is 0.52%. The type of helminth that infected cattle in 2020-2022 is Paramphistomum sp., with as many as 87, 48, and 205 cases, with the highest incidence in Bungo Regency, namely 23 cases, while Jambi City, namely, 21 and 51 cases. Conclusion: The highest incidence of helminthiasis in Jambi City, with the highest identified type of helminth egg, was Paramphistomum sp.